1989
DOI: 10.1007/bf01255815
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic peptides corresponding to the sequence of noxiustoxin indicate that the active site of this K+ channel blocker is located on its amino-terminal portion

Abstract: A nonapeptide Thr-Ile-Ile-Asn-Val-Lys-Cys-Thr-Ser (NTX1-9) and a decapeptide Met-Asn-Gly-Lys-Cys-Lys-Cys-Tyr-Asn-Asn (NTX30-39) corresponding to the N-terminal and C-terminal sequences respectively of Noxiustoxin (NTX) were synthesized by the solid phase method of Merrifield (1963). The first synthetic peptide (NTX1-9) was shown to be toxic to mice independently of the route of administration: intraperitoneally, subcutaneously or intraventricularly (100-200 micrograms/20 g mouse weight). The second (NTX30-39) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The rationale guiding the design of the mutants prepared and used in the present work was based on previous results: (a) our laboratory showed that the N‐terminal nonapeptide of NTX was toxic per se to mice [18, 19] or was able to recognize Ca 2+ ‐dependent K + channels from aortic tissue [20]; (b) several laboratories have shown that similar toxins, i.e. Charybdotoxin (ChTX) [11] and Agitoxin 2 (AgTX) [12] have a crucial lysine residue (K27 for Charybdotoxin), in equivalent positions as that of K28 for NTX, shown to be very important for channel blockade, and (c) the fact that amidation of asparagine at the C‐terminal region of NTX makes no difference on binding of radiolabeled NTX to brain synaptosome membranes [14], as well as that a synthetic decapeptide from the C‐terminal segment of NTX had no effect on binding displacement experiments [19].…”
Section: Resultsmentioning
confidence: 99%
“…The rationale guiding the design of the mutants prepared and used in the present work was based on previous results: (a) our laboratory showed that the N‐terminal nonapeptide of NTX was toxic per se to mice [18, 19] or was able to recognize Ca 2+ ‐dependent K + channels from aortic tissue [20]; (b) several laboratories have shown that similar toxins, i.e. Charybdotoxin (ChTX) [11] and Agitoxin 2 (AgTX) [12] have a crucial lysine residue (K27 for Charybdotoxin), in equivalent positions as that of K28 for NTX, shown to be very important for channel blockade, and (c) the fact that amidation of asparagine at the C‐terminal region of NTX makes no difference on binding of radiolabeled NTX to brain synaptosome membranes [14], as well as that a synthetic decapeptide from the C‐terminal segment of NTX had no effect on binding displacement experiments [19].…”
Section: Resultsmentioning
confidence: 99%
“…Significant benefits of chemical assembly include the production of non-native analogs [61,62], truncated [63,64,65] or point mutated toxins [5,66], chimeric compounds [8,67], biotinylated molecules [5,68], toxins labeled with fluorescent moieties [69,70], pseudo peptides [71,72,73], or those containing D-amino acids [39,74], compounds which would prove difficult or impossible to produce using recombinant technology [75]. These approaches enhance functionality, utility and breadth of scorpion toxins in biomedical research.…”
Section: Synthetic Toxin Productionmentioning
confidence: 99%
“…This resulted in the production of native-like material and truncated versions of NTX [65]. The biologically active, synthetic peptide was desirable for two reasons, (i) a large number of scorpions (~1000) would need to be milked in order to obtain quantities of material suitable for pharmacological experimentation (1 mg), as NTX represents only a fraction of the total protein (~1%) in the crude venom extract [26], and (ii) truncated versions of NTX do not occur naturally [65]. Noxiustoxin and the truncated terminal peptide segments were assayed and their pharmacological activity compared.…”
Section: Synthetic Toxin Productionmentioning
confidence: 99%
“…122 Synthetic peptides corresponding to the first nine residues from the N terminus of noxiustoxin were reported to retain some K + channel-blocking activity. 123 Noxiustoxin has been used to prepare an affinity chromatography column in order to isolate binding sites from squid axonal membranes.124 The affinitypurified proteins could be incorporated into planar lipid bilayers, which then displayed channel activity consistent with the presence of voltage-activated K + channels. The majority of events corresponded to a single-channel conductance of 11 pS, and they were blocked by noxiustoxin and tetraethylammonium.…”
Section: Toxins Blocking Voltage-dependentmentioning
confidence: 99%